If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(60+n)/3=(84+n)/15
We move all terms to the left:
(60+n)/3-((84+n)/15)=0
We add all the numbers together, and all the variables
(n+60)/3-((n+84)/15)=0
We calculate fractions
n/()+(-((n+84)*3)/()=0
We calculate terms in parentheses: +(-((n+84)*3)/(), so:We get rid of parentheses
-((n+84)*3)/(
We multiply all the terms by the denominator
-((n+84)*3)
We calculate terms in parentheses: -((n+84)*3), so:We get rid of parentheses
(n+84)*3
We multiply parentheses
3n+252
Back to the equation:
-(3n+252)
-3n-252
Back to the equation:
+(-3n-252)
n/()-3n-252=0
We multiply all the terms by the denominator
n-3n*()-252*()=0
We add all the numbers together, and all the variables
n-3n*()=0
| x-4=4x-26 | | 7b^2+4=627 | | 7b^2+4=672 | | x/3+x/4+x/6+24000=x | | 3m^2+10m-7=0 | | 7p^2-9=-2 | | 26=2m^2+8 | | 15x-20=7x+2 | | 3/x+1=4/16 | | 3x^2=13+2x | | 70x+19x+2=180 | | 53x+107=1019 | | 2*n=4+3 | | p=52149/(1+.07/12)^60 | | 9p^2+3p^2+15p+5=0 | | 9+n=15-3 | | 7+n=9+2 | | 3x(-)8=28 | | 3÷x-7=2 | | 4x-3/5=2x-4/10 | | 2n^2+2n-12=n^2+6-n | | (1/9)^3x=27^3x+1 | | 31x-7=12 | | y=-4₩5×-2 | | 2÷(c+3)=-5÷(c-1) | | 43/7x-31/2=12 | | 1/2(3x+4)(2x+1)=39 | | 0=7c+13 | | 20y^2-37y-18=0 | | 3.14×22.5=a | | -2x-13.8x=-8x-(6x+1) | | 9x^2+18x-53=0 |